Implementasi Kebijakan Merdeka Belajar Pada Mata Pelajaran Pendidikan Agama Hindu Dan Budi Pekerti Di Sekolah Vidya Karuna Ubung Kaja Denpasar - Kananda, Febri Vive; Sudarsana, I Ketut; Hendrawathy Putri, I Dewa Ayu (Kamaya: Jurnal Ilmu Agama, 2024)
Education must adapt to the needs of each era, one of which is an education system that can encourage adaptation to change and become lifelong learners. Hindu Religious Education is one of the media to transform divine and humanitarian values ​​in social, national, and state life which is developed to create an advanced generation in various sectors of life. Vidya Karuna School uses the merdeka belajar policy reference as a direction for future learning that provides opportunities for teachers and students to think freely, innovate freely, and learn independently and creatively to achieve the learning objectives of Hindu Religious Education and Character Education. The purpose of this study was to determine how the implementation, obstacles and efforts, and implications of the merdeka belajar policy are in the subjects of Hindu Religious Education and Character Education. The data collection methods used in this study were observation, interviews, and literature studies. The data that had been collected were analyzed using a qualitative descriptive analysis method with steps of reduction, data presentation, drawing conclusions, and presenting the results of data analysis. Based on the overall data obtained, it can be seen that in implementing the merdeka belajar policy in Hindu Religion and Character Education, there are several stages, namely the process, implementation, and evaluation. To implement the merdeka belajar policy in the subjects of Hindu Religion and Character Education at Vidya Karuna School, teachers use several methods and strategies in learning that are adjusted to the stage of child development at each phase. The goal is to make Hindu Religion learning more effective, and interesting, and can create a pleasant learning atmosphere. In the implementation of the merdeka belajar policy, there are also several obstacles consisting of internal and external obstacles. The implications of the merdeka belajar policy in the subjects of Hindu Religion and Character Education at Vidya Karuna School are implemented using the 4C approach, developing innovative learning models.